Factors Influencing the Use of Recommendation Systems for Elderly Research in Thailand - Molee, A-Phorn; Chansanam, Wirapong (Journal of information science theory and practice, 2025)
This study examines factors influencing the use of recommendation systems for elderly research in Thailand through a quantitative research design. The target population comprises researchers experienced in elderly studies from 2012 to 2022, totaling 348 participants. Data were collected via a validated questionnaire (Cronbach's alpha=0.955). Employing an extended the Unified Theory of Acceptance and Use of Technology 2 model, the study investigates system use behavior (SUB) based on seven core factors: Performance expectancy (PEF), effort expectancy (EFF), social influence, personal innovativeness (INN), hedonic motivation (MOT), facilitating conditions (FAC), and intention behavior (IBV), alongside three additional factors-system quality (SQU), information quality (IQU), and trust. Multiple correlation and regression analyses reveal statistically significant influences (p<0.05) from eight factors. SQU, PEF, EFF, MOT, FAC, and IBV positively influence SUB. Conversely, IQU and INN negatively affect system usage. The predictive model is expressed as: SUB=1.195+0.116 (SQU)-0.268 (IQU)+0.134 (PEF)+0.181 (EFF)-0.406 (INN)+0.137 (MOT)+0.097 (FAC)+0.866 (IBV). These findings underscore the importance of optimizing system features and recognizing the distinct needs and expectations of elderly research communities to enhance the effectiveness of these recommendation systems.